Measuring resistance index in patients with BPH and lower urinary tract symptoms - Ozdemir, H; Onur, R; Bozgeyik, Z; Orhan, I; Ogras, MS; Ogur, E (Wiley, 2005)
Purpose. To assess the correlation between resistance index (RI) measured in different zones of the prostate and other more commonly used parameters of benign prostatic hyperplasia (BPH). Methods. Twenty-six male patients who underwent a detailed evaluation for lower urinary tract symptoms suggestive of BPH were examined with transrectal (TRUS) color Doppler sonography (CDS). The correlation between RI in various prostate zones, and various urinary flow rates, and the International Prostate Symptom Score (IPSS), and prostatic volume measured by TRUS was determined. Results. No significant difference in RI was observed between right and left transition (TZ) and peripheral zones (PZ) in the prostate (P > 0.05). There was a significant correlation between mean RI and maximum urinary flow rate (Qmax) and mean RI in both zones (r = -0.48 for TZ and r = -0.39, P < 0.05 for PZ). Individual measurements in left and right TZ RI were also correlated with Qmax. There was a correlation between prostatic volume and both the right (P < 0.05, r = 0.56) and the left (P < 0.05, r = 0.58) TZ RI, respectively. Conclusion. Our results demonstrate the potential value of RI measurement in the evaluation of patients with lower urinary tract symptoms suggestive of BPH. (c) 2005 Wiley Periodicals, Inc.
Keywords: benign prostatic hyperplasia; diagnosis; power Doppler ultrasonography; color Doppler ultrasonography; resistance index; LUTS; transition zone; peripheral zone